2012
DOI: 10.18869/acadpub.johe.1.3.124
|View full text |Cite
|
Sign up to set email alerts
|

Lower immunity to tetanus in cigarette smoker subjects

Abstract: Received: February 2013, Accepted: October 2013 Background: Cigarette smoking has been linked with the suppression of immune responses and increased susceptibility to numerous infections in humans. Tetanus is also a major public health problem in many countries. The aim of the present study was to evaluate the serum levels of antitetanus toxin antibodies in cigarette smoking and healthy non-smoking people. Materials and Methods: A total of 100 cigarette smokers and 100 age-matched healthy nonsmoker individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In addition, the same outcome was confirmed with mutually aOR. The effect of smoking on the immune response found in this trial is in line with published results [12]. We found that the chance of achieving a fourfold rise in antibodies was decreased in smokers by almost 90% compared with non-smokers.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the same outcome was confirmed with mutually aOR. The effect of smoking on the immune response found in this trial is in line with published results [12]. We found that the chance of achieving a fourfold rise in antibodies was decreased in smokers by almost 90% compared with non-smokers.…”
Section: Discussionsupporting
confidence: 92%
“…The finding that current smoking was associated with a smaller probability of being seropositive was counter-intuitive under the hypothesis that smoking was associated with a less healthy attitude and more risky behavior. We thus conducted several sensitivity analyses in the search for potential confounding effects and questioning the possibility of whether an impaired ability to mount antibodies might explain our observations [21,22] (Supplementary Note): we found stable associations across age groups and sex (Supplementary Table S9a) and a dose-response effect (Supplementary Figure S2). The association persisted when comparing the known infected with the known uninfected (i.e., restricting to the n = 501 tested, OR = 0.35 for current smoking associated with positive versus negative PCR-test report), which is in line with a hypothesis that current smoking was associated with a lower risk of infection (Supplementary Table S9b).…”
Section: Association Of Demographic and Lifestyle Factors With Seropositivitymentioning
confidence: 99%
“…An alternative explanation is a decreased antibody response after infection among smokers compared to non-smokers, in line with a suppressed immune system. Interactions between smoking and the immune system are widely acknowledged (e.g., [ 17 , 18 , 19 ]) and also hypothesized for immune responses to SARS-CoV-2 [ 7 , 20 ]. An evaluation of differences in antibody response by smoking status is lacking so far.…”
Section: Introductionmentioning
confidence: 99%